MINING SAFETY DEVICE - BALAKRISHNA, B.; RAJU, K.; RAO, B.VENKATESWER; PRANEETH, K.SAI; VIDYA, K. (The journal of contemporary issues in business and government, 2022)
The project is aimed at designing a miner safety alert system. Mining work is one of the most dangerous work to do. So we as the engineers we are doing our small part by trying to reduce this danger. We are designing a safety device for the mining workers using Zigbee transmitter and receiver. We are using temperature sensors so that if any change in temperature it can easily be detected. We are also using gas sensor through which a small amount of gas leakage can also be detected. We are installing a button so that in case of emergency the mine workers can press the button which gives the alert at the base so that the rescue teams can easily reach the affected area with-in the time , so the people who are in danger zone are saved with in the time. Temperature and gas leakage will be monitored by emergency team all the time, so that in case of any danger they can immediately take action at particular area. Mines that are deeper, the more dangerous it could be to be running jobs. There are challenges related to leaving a mine in case of a crisis. So by using this device many lives can be saved and dangers can be avoided.